Factors affecting the adoption of RFID in the food supply chain: a systematic literature review - Masekwana, Fundiswa; Jokonya, Osden (Frontiers in Sustainable Food Systems, 2025)
The unsustainability of the current food system raises food security concerns worldwide due to the population’s increased demand for fresh food and food safety. Unsafe food incidents lead to a high risk of poverty and economic loss. This includes food waste, safety, and security during the sustainable food system process from farm production to consumer. There is a need to implement a fast traceability system like Radio Frequency Identification (RFID) in the sustainable food system to ensure food quality and safety, meet customer demands, and achieve Sustainable Development Goals (SDGs): 1—No poverty, 2—Zero hunger and 13—Climate action for 2030 target. The study objective was to explore the factors that affect the adoption of Radio Frequency Identification (RFID) in the food supply chain. The study adopted the TOE (technology-organization-environment) framework to explore factors that affect RFID adoption in the food supply chain. The study utilized a systematic literature review to examine the TOE factors influencing the adoption of RFID in the food supply chain. The results indicate that technological (complexity, cost, and security), organizational (technical skill and management support), and environmental (maintenance and support, IT policies and regulations) are the major factors that affect the adoption of RFID in the sustainable food system industry. The study recommends organisations intending to adopt RFID allocate enough resources and be prepared to overcome RFID adoption external challenges. The study concludes that technological factors, organizational factors, and environmental factors are important factors for RFID adoption in the food supply chain. However, further empirical studies are necessary to overcome the challenges of systematic literature review based on secondary data and convenience sampling.